AN ANALYTICAL TEMPERATURE SOLUTION ANALYSIS FOR A MULTILAYER HEAT CONDUCTION PROBLEM - Oliveira, G. C.; Fernandes, A. P.; Guimarães, G. (Revista de Engenharia Térmica, 2014)
This paper presents a method of obtaining an analytic temperature solution for a two-layer heat conduction problem. Obtaining the temperature analytical solution for a multilayer heat conduction problem is not a direct method. The way to indentify the eigenvalues and to derive the Green function solution equation requires a different treatment since there are more than one domain to solve. This work presents a solution of a thermal twolayer problem based on Green’s functions.